A comprehensive evaluation of energy storage options for better sustainability. (18th May 2018) - Acar, Canan
Summary: Due to ever increasing global energy demand and the limited nature of fossil fuel reserves, there has been tremendous research and development studies in the literature, focusing on alternative and clean energy resources and systems. Renewables are the promising choice when it comes to addressing some critical energy issues such as climate change and energy security. However, renewables have intermittent and discontinuous supplies; hence, they need to be stored in ways that are affordable, reliable, flexible, clean, safe, and efficient. As a result, energy storage is becoming a crucial step to build innovative energy systems for a sustainable future. Energy can be stored in many forms, from electrical to chemical (eg, hydrogen), or electrochemical, thermal, electromagnetic, etc. Each form consists of different technologies, some of which are already commercially mature while others are at early research and development stages. Each of these options can be tailored to meet different end users' needs at different scales. Therefore, this study aims to conduct a comprehensive review on the most recent status of energy storage options, along with the requirements of various end users, and characteristics of smart energy storage systems. The main objective is to summarize the performance evaluation statuses of mechanical, electrochemical, chemical, thermal, and electromagnetic energy storage technologies. The selected performance measures are capacity flexibility, energy arbitrage, system balancing, congestion management, environmental impact, and power quality. In the end, some key recommendations and future directions for energy storage systems are provided.